STRATEGI RUSDI DALAM MEMENANGKAN PEMILIHAN KEPALA DESA SIALANG JAYA KECAMATAN BATANG TUAKA KABUPATEN INDRAGIRI HILIR TAHUN 2019 - Saiful Bahri; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is entitled "Rusdi's strategy in winning the Sialang Jaya Village Head Election, Batang Tuaka District, Indragiri HIlir Regency in 2019". The purpose of this study was to find out Rusdi's strategy as the elected Village Head in the 2019 village head election, where Rusdi was a candidate from outside competing with two candidates from the village natives. This strategy is a political strategy to achieve victory in the village head election contestation. Political strategy here is an approach to political communication carried out by contestants or prospective candidates to win political contestations. This study uses a qualitative research approach, with data analysis techniques carried out in a descriptive way. Selection of informants using purposive sampling and data collection using in-depth interviews and documentation. To see the candidate's winning strategy, Peter Schrolder's theory of political strategy is used, namely an offensive strategy (attacking). Based on this theory, it can clarify Rusdi's strategy in winning the 2019 Sialang Jaya village head election. The results of the research are Rusdi's offensive strategy, namely by approaching village elites and the community directly, disseminating the vision, mission and work program and giving political promises, forming a positive image in the community and providing assistance to residents, and using the help of communication media such as installing baleho or banner. The success of Rusdi's strategy to expand and penetrate the market to gain community support led Rusdi as the elected village head in the election of the Sialang Jaya Village Head, Batang Tuaka District, Indragiri Hilir Regency for the 2019-2025 period. Keywords: Political Strategy, Village Head Election, Offensive Strategy